1992
DOI: 10.1271/nogeikagaku1924.66.1007
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Pesticide Residues in Vegetables and Fruits and Removal by Washing.

Abstract: Marketed vegetables and fruits contaminated by organophosphorus, organochlorine, or carba mate pesticides were cut into several regions (fruit stalk, pericarp, fruit receptacle, tissue around the stalk cavity, etc.) and the concentration of the pesticide residues in each region was assayed. In fruits and fruit-type vegetables, the concentra tion of the pesticide residue was higher in the fruit stalk and near the epidermis (exocarp and fruit receptacle) than in the sarcocarp or peri carp. In leaf vegetables, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…However, only 18-55% endosulfan was reduced by washing. The removal rates of pesticide residues of dieldrin and heptachlor epoxide in pumpkins and cucumbers, by washing with water or 0.1% liquid detergent were 8-52% and 19-67%, respectively (Yoshida et al 1992). Removal of the fruit stalk, exocarp and tissue around stalk cavity of fruits and fruit-type vegetables and washing of leaves with water or dilute detergent solution were necessary to decrease the intake of pesticide residues from vegetables and fruits.…”
Section: Preparatory Stepsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, only 18-55% endosulfan was reduced by washing. The removal rates of pesticide residues of dieldrin and heptachlor epoxide in pumpkins and cucumbers, by washing with water or 0.1% liquid detergent were 8-52% and 19-67%, respectively (Yoshida et al 1992). Removal of the fruit stalk, exocarp and tissue around stalk cavity of fruits and fruit-type vegetables and washing of leaves with water or dilute detergent solution were necessary to decrease the intake of pesticide residues from vegetables and fruits.…”
Section: Preparatory Stepsmentioning
confidence: 97%
“…In fruits and fruittype vegetables, the concentration of pesticide residue was higher in the fruit stalk and near the epidermis (exocarp and fruit receptacle) than in the sarcocarp or pericarp. In leaf vegetables, concentration of the pesticide residue was higher in outer leaves than in inner ones (Yoshida et al 1992). The leaching of pesticides from the surface of fruits and leafy commodities is due to their solubility in water (Jaggi et al 2000).…”
Section: Dissipation Vis-à-vis-localization Of Pesticide Residues In mentioning
confidence: 99%
“…The removal rates of 8-52% and 19-67%, for pesticide residues of dieldrin and heptachlor epoxide in pumpkins and cucumbers, by washing with water or 0.1% liquid detergent (respectively) have been reported [17].…”
Section: Introductionmentioning
confidence: 99%
“…1) Pesticide residues in foods and crops are a direct result of the application of pesticides to crops growing in field, and, to a lesser extent, from pesticide residues remaining in the soil. 2) Yoshida et al 3) reported the removal rates of pesticide residues in fruits and vegetables by washing with water. Water washing has been reported to remove malathion residues from vegetables.…”
Section: Introductionmentioning
confidence: 99%